Estudo do efeito da adição de solventes nos parâmetros físico-químicos que caracterizam a qualidade da gasolina automotiva - Almeida, Selmo Queiroz (2002)
The effects of the addition of solvents in the quality of automotive gasoline verified in the physico-chemical parameters were studied in this work; through a distillation curve and an infrared analytical procedure to determine the octane number. The solvents tested were oil diesel, kerosene, turpentine spirit, thinner, rafinado and methanol. The analysis consisted of the addition of different amounts of these solvents in automobile gasoline in order to discover any alterations related to the brazilian specifications. The results obtained allowed the verification of the addition of any solvents which modified the profile of the distillation curve, some times exceeding the specifications. It was also possible to verify that the addition of solvents in gasoline can, depending on the solvent, diminish or to increase the octane of the same gasoline, but in no case put the gasoline out of the specifications in regards to this parameter. It was proven experimentally that the added amount of solvent is dependent, not only on the type of solvent, but also on the composition of the gasoline. Gasoline with a larger amount of light components needs a bigger amount of heavy solvent for it to exceed the specifications. The results showed that gasoline, even within specifications, may have been adulterated. In the end of this work, it was done a study where showed that with a blend containing only 15% of gasoline type A and different solvents is possible to formulate a gasoline type C within brazilian specifications. This study it comes to inform, ahead of the current regulatory conjuncture, the problems found in the fuel sector, due to addition of solvent in the automotiva gasoline. In this direction, it was verified that a gasoline can be specified e, at the same time,adulterated.